1997
DOI: 10.1073/pnas.94.1.237
|View full text |Cite
|
Sign up to set email alerts
|

Terminal differentiation of human liposarcoma cells induced by ligands for peroxisome proliferator-activated receptor γ and the retinoid X receptor

Abstract: Induction of terminal differentiation represents a promising therapeutic approach to certain human malignancies. The peroxisome proliferator-activated receptor ␥ (PPAR␥) and the retinoid X receptor ␣ (RXR␣) form a heterodimeric complex that functions as a central regulator of adipocyte differentiation. Natural and synthetic ligands for both receptors have been identified. We demonstrate here that PPAR␥ is expressed at high levels in each of the major histologic types of human liposarcoma. Moreover, primary hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
393
2
9

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 592 publications
(420 citation statements)
references
References 35 publications
(44 reference statements)
16
393
2
9
Order By: Relevance
“…In vivo study on xenograft of human tumours in immunodeficient mice followed by troglitazone treatment also provided similar results (Elstner et al, 1998;Kubota et al, 1998;Sarraf et al, 1998). Ligand-mediated PPARγ activation in those cancer cells induced cell cycle arrest (Tontonoz et al, 1997;Brockman et al, 1998;Sugimura et al, 1999;, differentiation (Tontonoz et al, 1997;Kubota et al, 1998;Mueller et al, 1998;Sarraf et al, 1998;Chang and Szabo, 2000), and apoptosis (Elstner et al, 1998;Clay et al, 1999;Keelan et al, 1999;Sato et al, 2000) or nonapoptotic cell death (Kubota et al, 1998;Butler et al, 2000). Recently, troglitazone has been used in clinical trial for the patients with advanced liposarcoma (Demetri et al, 1999) and for patients with advanced prostate cancer (Hisatake et al, 2000;Mueller et al, 2000).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…In vivo study on xenograft of human tumours in immunodeficient mice followed by troglitazone treatment also provided similar results (Elstner et al, 1998;Kubota et al, 1998;Sarraf et al, 1998). Ligand-mediated PPARγ activation in those cancer cells induced cell cycle arrest (Tontonoz et al, 1997;Brockman et al, 1998;Sugimura et al, 1999;, differentiation (Tontonoz et al, 1997;Kubota et al, 1998;Mueller et al, 1998;Sarraf et al, 1998;Chang and Szabo, 2000), and apoptosis (Elstner et al, 1998;Clay et al, 1999;Keelan et al, 1999;Sato et al, 2000) or nonapoptotic cell death (Kubota et al, 1998;Butler et al, 2000). Recently, troglitazone has been used in clinical trial for the patients with advanced liposarcoma (Demetri et al, 1999) and for patients with advanced prostate cancer (Hisatake et al, 2000;Mueller et al, 2000).…”
mentioning
confidence: 74%
“…Further studies are also required to reveal whether inhibition of the p27 Kipl or p18 Ink4c increase could inhibit the growth arrest in Hep G2 as found in PK-1 cells . PPARγ ligands have been shown to drive differentiation process in various malignant cells (Tontonoz et al, 1997;Kubota et al, 1998;Sarraf et al, 1998;Chang and Szabo, 2000). When we investigated the expression of AFP and albumin in Hep G2 cells after treatment with troglitazone, we found that there was a dosedependent decrease in the AFP expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported that 15-deoxy-D 12,14 -prostaglandin J 2 (15d-PGJ 2 ), the most potent endogenous ligand for PPARg, and the synthetic PPARg ligand thiazolidinedione (TZD) can induce terminal differentiation and growth inhibition of human liposarcoma (Tontonoz et al, 1997), breast (Elstner et al, 1998;Yee et al, 1999), prostate (Kubota et al, 1998), colon (Sarraf et al, 1998;Kitamura et al, 1999), gastric (Takahashi et al, 1999;Sato et al, 2000), lung (Chang and Szabo, 2000;Tsubouchi et al, 2000), and pancreas (Motomura et al, 2000;Elnemr et al, 2000) cancer cells, as well as hepatoma cells (Koga et al, 2001) in vitro and in vivo. The in vivo induction of histological and biochemical differentiation of liposarcomas by clinical trial of troglitazone administration was reported by Demetri et al (1999).…”
mentioning
confidence: 99%
“…It has been investigated whether PPAR␥ might be a useful target for the treatment of tumors. Several studies have shown that TZDs can lead to growth inhibition in liposarcoma, 12 breast cancer, 13,14 colon cancer, [15][16][17] prostatic cancer 18 and gastric cancer. 19 In the present study, we observed the expression of PPAR␥ and investigated the effects of TZD and their mechanism on pancreatic cancers.…”
mentioning
confidence: 99%